The Global Prevalence of Daptomycin, Tigecycline, and Linezolid-Resistant Enterococcus faecalis and Enterococcus faecium Strains From Human Clinical Samples: A Systematic Review and Meta-Analysis - Dadashi, Masoud; Sharifian, Parastoo; Bostanshirin, Nazila; Hajikhani, Bahareh; Bostanghadiri, Narjess; Khosravi-Dehaghi, Nafiseh; van Belkum, Alex; Darban-Sarokhalil, Davood (Frontiers in Medicine, 2021)
Background and aim: The predominant species of the Enterococcus genus, Enterococcus faecalis (E. faecalis) and Enterococcus faecium (E. faecium) are cause a wide variety of serious infections in the world. Therefore, the expansion of antimicrobial resistance in the Enterococcus genus is one of the most important global concerns. This study was conducted to investigate the prevalence of resistance to linezolid, tigecycline, and daptomycin among enterococcal strains isolated from human clinical specimens worldwide. Methods: Several databases including web of science, EMBASE, and Medline (via PubMed), were searched and reviewed for published original research articles between 2000 and 2020. A total of 114 studies worldwide that address E. faecalis and E. faecium resistance to linezolid, tigecycline, and daptomycin were analyzed by STATA software. Results: The overall prevalence of E. faecalis and E. faecium to the antibiotics was reported to be 0.9% and 0.6%, respectively. E. faecalis and E. faecium were more resistant to the linezolid (2.2%) and daptomycin (9%), respectively. The prevalence of E. faecalis strains resistant to these antibiotics in the Americas was higher than in Asia, whilst the prevalence of antibiotic-resistant E. faecium strains was higher in Asia (43.6%) compare to other continents. Accordingly, the prevalence of linezolid resistant E. faecalis was higher in Asia (2.8%), while linezolid resistant E. faecium was higher in the Americas (3.4%). Regarding tigecycline resistance, a higher prevalence of E. faecalis (0.4%) and E. faecium (3.9%) was reported in Europe. Conclusion: Despite the rising resistance of enterococci to antibiotics, our results show tigecycline, daptomycin, and linezolid can still be used for the treatment of enterococcal infections worldwide.